Capillaroscopy and Endopat – Helpful Methods for the Early Assessment of Increased Cardiovascular Risk in Anorexia Nervosa? - Ferencova Nikola; Visnovcova Zuzana; Ondrejka Igor; Tonhajzerova Ingrid (Acta Medica Martiniana, 2023)
Anorexia nervosa (AN) as a life-threatening eating disorder is linked to a high mortality risk with many deaths attributable to cardiovascular etiology. Cardiovascular complications in AN include structural as well as functional cardiac alterations, hemodynamic changes, and peripheral vascular abnormalities. Despite the fact that peripheral vascular abnormalities are not identified as a major AN complication, several manifestations of peripheral vascular dysregulation including Raynaud's phenomenon and endothelial dysfunction have been described and, therefore, warrant attention. This article briefly summarizes so far findings of microvascular alterations in AN patients and presents easily accessible and non-invasive procedures for a microvascular evaluation such as capillaroscopy and endothelium-related peripheral arterial tone (EndoPAT) which could be involved in the clinical diagnostic process for the earliest identification of an increased risk of later cardiovascular complications.